Analysis of Methods and Approaches in Project Management in Non-Formal Education in Indonesia - Ahmad Ridwan; Enni Sustiyatik; Anton Respati Pamungkas (Journal of Nonformal Education, 2024)
Non-formal education in Indonesia plays an important role in the development of human resources who are able to adapt to changing times. Project management in non-formal education is key to increasing the effectiveness and efficiency of the educational programs offered. However, there are challenges in the application of conventional project management methods due to the dynamics and specific needs of non-formal education that often change. This paper aims to analyze the methods and approaches in project management used in non-formal education in Indonesia, as well as identify strategies that can improve the effectiveness and efficiency of non-formal education programs. The method used is a literature review, where data is collected from Scopus standard journals, related books, and policy documents. The analysis is carried out through the organization, categorization, and interpretation of relevant information to evaluate the effectiveness of existing project management methods. The findings show that the Critical Chain Project Management (CCPM) method is more adaptive and flexible compared to the Critical Path Method (CPM) and Waterfall methods, which tend to be rigid and linear. CCPM allows for more efficient resource management and realistic scheduling, in line with the dynamic needs of non-formal education. This study implies that non-formal educational institutions in Indonesia need to adopt more flexible and adaptive project management methods. The novelty of this study lies in the comparative analysis between conventional and adaptive project management methods, as well as strategic recommendations for the implementation of CCPM in the context of non-formal education. The contribution of this research is to provide new insights into the application of project management in non-formal education and to offer a framework that educational project managers can use to improve the effectiveness of their programs. This study also provides recommendations for the development of project management training that is in accordance with the needs of non-formal education in Indonesia.